2008
DOI: 10.1007/s11172-008-0096-6
|View full text |Cite
|
Sign up to set email alerts
|

Alkyl 3-fluoroalkyl-3-oxopropionates in reactions with azolyldiazonium salts

Abstract: Alkyl 3 fluoroalkyl 3 oxopropionates react with antipyrinyldiazonium chloride to form 2 antipyrinylhydrazono 3 fluoroalkyl 3 oxopropionates. The use in these reactions of hetaryldiaz onium salts, containing NH group in the α position, leads to alkyl 7 fluoroalkyl 7 hydroxy 4,7 dihydroazolo[5,1 c]triazine 6 carboxylates. 3 Amino 1H 1,2,4 triazole, 3 amino 4 ethoxycar bonyl 1H pyrazole, and 5 amino 4 ethoxycarbonyl 1H imidazole were used as the heterocyclic component.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…In the case of 3-methyl-1H-pyrazole-5-amine 5e we did not manage to isolate hydrosulfate salt 6e as a solid. Therefore, it was alternatively generated from aminopyrazole 5e by reaction with sodium nitrite in an aqueous solution of HBF 4 at low temperature (Scheme 2) and tetrafluoroborate salt 6e was used in situ in further studies. Enamines 8a-f were prepared by treatment of the corresponding 5-methylthiadiazole-4-carboxylate 7a,b or alkyl 5-methyl-3-arylisoxazole-4-carboxylates esters 7c-f with DMF-DMA in the presence of N-methylimidazole under reflux for six hours as has been reported earlier 33,34 (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the case of 3-methyl-1H-pyrazole-5-amine 5e we did not manage to isolate hydrosulfate salt 6e as a solid. Therefore, it was alternatively generated from aminopyrazole 5e by reaction with sodium nitrite in an aqueous solution of HBF 4 at low temperature (Scheme 2) and tetrafluoroborate salt 6e was used in situ in further studies. Enamines 8a-f were prepared by treatment of the corresponding 5-methylthiadiazole-4-carboxylate 7a,b or alkyl 5-methyl-3-arylisoxazole-4-carboxylates esters 7c-f with DMF-DMA in the presence of N-methylimidazole under reflux for six hours as has been reported earlier 33,34 (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to aromatic diazonium salts, they can couple with a very broad range of aromatic and heteroaromatic compounds 1,2 as well as with active methylene reagents [3][4][5][6] to form azo compounds and hydrazones, respectively. On the other hand, similarly to diazoalkanes, they react with alkenes, [7][8][9][10][11][12][13][14] alkynes, [8][9][10] enamines, 10,12,13,15 ynamines, 7,12,13,16 isocyanates [17][18][19][20][21][22][23] and isothiocyanates 24,25 to furnish a huge variety of heterocyclic compounds.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study showed the structure of hetaryl component to exert determinative influence on the result of azo coupling between fluoroalkyl‐containing 1,3‐dicarbonyl compounds and hetaryldiazonium salts. Thus, the reactions of polyfluoroalkyl‐containing 1,3‐diketones and 3‐oxo esters with hetaryldiazonium chlorides having the fragment NH in α‐position (1,2,4‐triazolyl‐3‐, 4‐ethoxycarbonylpyrazolyl‐3‐, and 4‐ethoxycarbonylimidazolyl‐5‐diazonium chlorides) [23–25] gave the stable 4‐hydroxy‐4‐polyfluoroalkyl‐1,4‐dihydroazolo[5,1‐ c ][1,2,4]triazines rather than expected open‐chain 2‐hetarylhydrazono‐1,3‐dicarbonyl compounds. At the same time, antipyrinyldiazonium salt in these reactions resulted in 2‐antipyrinylhydrazono‐1,3‐dicarbonyl compounds [26].…”
Section: Introductionmentioning
confidence: 99%